2019
DOI: 10.1007/s00508-019-1448-y
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressives and biologics during pregnancy and lactation

Abstract: SummaryAn increasing and early-onset use of immunosuppressives and biologics has become more frequently seen among patients with inflammatory bowel diseases (IBD) and rheumatic disorders. Many women in their childbearing years currently receive such medications, and some of them in an interdisciplinary setting. Many questions arise in women already pregnant or wishing to conceive with respect to continuing or discontinuing treatment, the risks borne by the newborns and their mothers and long-term safety. Toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 106 publications
0
17
0
4
Order By: Relevance
“…It has been demonstrated that prenatal exposition on TNFi does not influence development of T or B cells [ 28 , 29 ]. Yet, there are some safety concerns regarding risk of developing serious infections, such as tuberculosis due to detectable anti-TNF antibodies in infants sera [ 30 ]. According to the EULAR experts, some TNFi including certolizumab (CTZ) and ETN have been approved during pregnancy [ 31 , 32 ].…”
Section: Bdmards Based On Cytokine-targeted Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that prenatal exposition on TNFi does not influence development of T or B cells [ 28 , 29 ]. Yet, there are some safety concerns regarding risk of developing serious infections, such as tuberculosis due to detectable anti-TNF antibodies in infants sera [ 30 ]. According to the EULAR experts, some TNFi including certolizumab (CTZ) and ETN have been approved during pregnancy [ 31 , 32 ].…”
Section: Bdmards Based On Cytokine-targeted Therapymentioning
confidence: 99%
“…Available data from two cohort studies, CRIB and CRADLE, led to its registration in EU for the treatment during pregnancy and breast-feeding periods [ 31 , 34 , 35 ]. Similarly, ETN due to its low concentrations in the breast milk and undetectable levels in newborn sera is considered by EULAR safe, although strength of evidence is lower in ETN than in CTZ [ 30 ]. Data on teratogenic effects of TNFi are limited and there is no strong evidence of potentially harmful effects, if used in preconception period [ 32 ].…”
Section: Bdmards Based On Cytokine-targeted Therapymentioning
confidence: 99%
“…Infliximab can be limited to the first trimester, adalimumab to the second trimester, and certolizumab to the third trimester since it has a low placental transfer. [ 98 99 100 ] Children whose mothers have been exposed to TNF blockers should not be given live-attenuated vaccines until 7 months of age. Other biologicals like rituximab and tocilizumab have limited data so they should be avoided in pregnancy.…”
Section: Immunosuppressive Agentsmentioning
confidence: 99%
“…To conclude, it is important to understand that pregnancy in uveitis is a challenging situation for uveitis specialists. [ 98 99 100 ]…”
Section: Immunosuppressive Agentsmentioning
confidence: 99%
“… 1 According to the 1979 FDA pregnancy risk categories, adalimumab is classified as pregnancy category B and appears to be safe to use by pregnant women during the first and second trimesters. 2 , 3 In 2015, the FDA replaced these categories by the Pregnancy and Lactation Labeling Rule (PLLR) which requires drug companies to present more information to providers and patients. 4 Guidelines published by the British Society for Rheumatology and the British Health Professionals in Rheumatology in 2016 recommended discontinuing adalimumab at the end of the second trimester of pregnancy.…”
Section: Introductionmentioning
confidence: 99%